Apoptosis Is a Demanding Selective Tool During the Development of Fetal Male Germ Cells - Bejarano, Ignacio; Rodríguez, Ana B.; Pariente, José A. (Frontiers in Cell and Developmental Biology, 2018)
Apoptosis is widely known to play a major role on diseases related to male infertility. Diseases of the male genital tract as defective spermatogenesis, decreased sperm motility, sperm DNA fragmentation, testicular torsion, varicocele and immunological infertility are strongly related to apoptotic cell death. Apoptosis must not be considered only as a fail on germ cell physiology or a secondary effect of certain pathologies and exogenous hazardous agents. Apoptosis orchestrates correct function and development of the male germ cell from the early embrionic stages of gonadal differentiation to the fertilization. In this review we have tried to adress a reading frame of the main knowledge about apoptosis in male germ cell development. Focussing on mechanisms concerning cellular apoptosis, which are independent of exogenous stimuli, we aimed to highlight that apoptosis is a selective instrument that guarantees the delivery of genetic message to offspring.